KESEJAHTERAAN PETANI PENGGARAP SAWAH PADA PENERAPAN AKAD MUZARA'AH DENGAN PENDEKATAN MAQASHID SYARI'AH DI TULUNGAGUNG - Dias Rizqi Wardani; Siti Inayatul Faizah (Universitas Airlangga, 2019)
Muzara’ah is the contract between farm workers and farm owners in which, cost of cultivations, seeds, and fertilizers are provided by the farm owners, meanwhile the farm workers have responsibility in giving their best efforts on cultivating the farmland. Later then, the harvest will be shared according to the contract that has been agreed. The purpose of this research is to describe farmer’s welfare in the village of Sodo after implementing Muzara’ah Contract with the Maqashid Sharia approach. This research approach is qualitative descriptive and uses case study as its strategy. Informants in this research are administrator from Krido Tani Farmers Association, The farm workers, and the farm owners. These informants determined by using purposive sampling technique. The data collection techniques are carried out through interview and direct observation. According to the research, it was shown that agricultural cooperation with Muzara’ah Contract has a role in improving farm workers’ welfare, viewed from the indicators of Maqasid Sharia.Keywords : Muzara’ah, Welfare, Farmer, Agricultural Cooperation